On the Identity of the Mirine Plant Bug Capsus bimaculatus Fabricius (Hemiptera: Miridae): New Synonyms, and Lectotype Designation - Melo, María Cecilia; Dellapé, Pablo Matías (Zootaxa, 2023)
The identity of Capsus bimaculatus Fabricius, 1803 is revised, as well as the varieties described by Berg (1892): Cal. (Par.) bimaculatus typicus, Cal. (Par.) bimaculatus vittatus, and Cal. (Par.) bimaculatus niger. The examination of all the bibliographies treating these names as well their type specimens resulted in the selection of a lectotype for C. bimaculatus, the synonymization of the three varieties described by Berg, selecting Taedia typica (Berg, 1892) as the valid name, and other taxonomic problems traced during the revision process are addressed.